2018
DOI: 10.14710/jab.v7i2.22693
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Peran Ganda, Stres Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Perempuan

Abstract: The work force in indonesia along the development of the changes. One of the amendments that is an influx of women in the work force. PT Phapros Tbk is one of the companies in Semarang have female employees who in 2013 until 2016 an up and down in attendance or absentee fluctuant. Both are permitted employee performance can be seen from the dual role, job stress and motivation work.The purpose of this research is to find influence the dual role, job stress and motivation work on performance female employees in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 0 publications
3
4
0
7
Order By: Relevance
“…This means that if the work-family conflict increases, the work motivation decreases, and vice versa. This result supports the previous findings (Nurismilida & Purba, 2018;Hapsari, 2015;Iswari & Pradhanawati, 2018;Twinarti et al, 2016;Medina, 2016), although there is also studies that give the opposite result, that work-family conflicts do not have a significant influence on work motivation (Adiyatwira & Supriyadi, 2017). Nurismilida and Purba (2018) found that work-family conflict has a significant influence on work motivation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This means that if the work-family conflict increases, the work motivation decreases, and vice versa. This result supports the previous findings (Nurismilida & Purba, 2018;Hapsari, 2015;Iswari & Pradhanawati, 2018;Twinarti et al, 2016;Medina, 2016), although there is also studies that give the opposite result, that work-family conflicts do not have a significant influence on work motivation (Adiyatwira & Supriyadi, 2017). Nurismilida and Purba (2018) found that work-family conflict has a significant influence on work motivation.…”
Section: Discussionsupporting
confidence: 88%
“…The first hypothesis in this study stated that work-family conflict has a significant negative influence on work motivation in Bank Jateng Syariah. This hypothesis refers to several prior researches (Nurismilida & Purba, 2018;Hapsari, 2015;Pradhanawati, 2018;Twinarti et al, 2016;Medina, 2016) who found negative and significant relationship between work-family conflict and work motivation.…”
Section: Discussionmentioning
confidence: 54%
“…Indicators of Z variable are somatic complaints, psychic complaints, and psychomotor disorders (Pandey, 2020). Female Employee Performance (Y) is the real achievements achieved by someone (Iswari & Pradhanawati, 2018). Indicators of Y variable are Initiative, mastering the job description, results achieved, the ability to cooperate, accuracy, compliance with orders, quality of work, level of accuracy of completion, and the quantity of work (Kurniawan, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Kinerja Karyawan adalah perilaku organisasi yang secara langsung berhubungan dengan aktivitas hasil kerja, pencapaian tugas, yang dimana istilah tugas berasal dari pemikiran aktivitas yang dilakukan oleh pekerjanya [24]. Secara umum faktorfaktor yang mempengaruhi kinerja adalah faktor individu yang meliputi kemampuan, keterampilan, latar belakang pribadi dan demografi; faktor psikologi yang terdiri dari persepsi, sikap, kepribadian, belajar dan motivasi; dan faktor organisasi yang terdiri dari sumber daya, kepemimpinan, imbalan, struktur dan desain pekerjaan [25]. Indikator kinerja terdiri dari Jumlah (kuantitas) pekerjaan, kualitas pekerjaan, ketepatan waktu, kehadiran, dan kemampuan kerja sama [26].…”
Section: Pendahuluanunclassified